Peran Konselor dalam Meningkatkan Kesejahteraan Psikologis Karyawan di Lingkungan Kerja - Hawwa Nasywa Aqillah; Suryani Suryani; Fahrurrozi Fahrurrozi; Agus Sukirno; Asep Furqonuddin (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
High work pressure, excessive workload, and work imbalance are the main factors causing stress, anxiety, and even depression in employees. In this case, the purpose of the research is to assess the urgency of the role of counselors in addressing psychological well-being problems in the workplace, as well as preventive measures, interventions to build an inclusive workplace culture and maintain psychological well-being. The literature review research method is used to explore a variety of relevant literatur. This research shows that actively engaging counselors to address psychological well-being issues in the workplace has a positive impact, improving job satisfaction, productivity, and employee retention.